2013
DOI: 10.1007/s12031-013-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Mutation in AFG3L2 Associated with Late Onset and Slow Progression of Spinocerebellar Ataxia Type 28

Abstract: SCA28 is caused by mutations in the AFG3L2 gene. This gene encodes a subunit of the mitochondrial metalloprotease AFG3L2 (AFG3-like protein 2). Clinical features of SCA28 include slow to moderate progressive ataxia, dysarthria, and additional symptoms such as nystagmus, slow saccades, and increased deep tendon reflexes. Here, we report on a novel AFG3L2 mutation in a patient with slowly progressive ataxia and a positive family history. The nucleotide change results in the substitution of an evolutionarily high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…The identified c.2011G>C nucleotide change is a novel variant determining the p.Gly671Arg alteration, which is pathogenic [8]. Table 2 demonstrates that the clinical phenotype of our patients is similar to that of the 82 earlier published SCA28 patients [6][7][8][10][11][12][13][14][15][16][17][18]. The lack of ophthalmoparesis, ptosis and slowing of saccades in our patients are the main differences, but these symptoms usually appear later in the course of the disease.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The identified c.2011G>C nucleotide change is a novel variant determining the p.Gly671Arg alteration, which is pathogenic [8]. Table 2 demonstrates that the clinical phenotype of our patients is similar to that of the 82 earlier published SCA28 patients [6][7][8][10][11][12][13][14][15][16][17][18]. The lack of ophthalmoparesis, ptosis and slowing of saccades in our patients are the main differences, but these symptoms usually appear later in the course of the disease.…”
Section: Discussionsupporting
confidence: 69%
“…Reviewing the available data from the scientific literature, only 9 out of 82 were described to had some kind of cognitive abnormality, without further specification [6][7][8][10][11][12][13][14][15][16][17][18]. Despite some limitations, including low case number and the fact that neuropsychological tests are poor localizers of brain pathology, the cognitive investigation performed in this study revealed slight abnormalities which may indicate the importance of integrity of cerebellar functioning in intact prefrontal activity [42].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that different mutations in various locations in the AFG3L2 gene may lead to different clinical phenotypes. Furthermore, the p.R468C mutation is located in exon 11, while all known ataxia-causing mutations, except one, are located in exons 15 and 16 of AFG3L2 (23,24) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the disease-related alterations were mapped to the region encompassing the peptidase domain (amino acids residues 654 through 700) (Edener et al 2010; Cagnoli et al 2010; Löbbe et al 2014; Smets et al 2014; Zühlke et al 2015). A number of heterozygous, substrate recognition-perturbing mutations in AFG3L2 were associated with autosomal dominant spinocerebellar ataxia type 28 (SCA28) (Di Bella et al 2010).…”
Section: M-aaa Proteasementioning
confidence: 99%